Fault tolerant hardware for high performance signal processing - Erdogan, S. S.; Shaneyfelf, Ted; Geok, See Ng; Abdul Rahman, Abdul Wahab (2008)
The approach described in this paper uses an array of Field Programmable Gate Array (FPGA) devices to implement a fault tolerant hardware system that can be compared to the running of fault tolerant software on a traditional processor. Fault tolerance is achieved is achieved by using FPGA with on the fly partial programmability feature. Major considerations while mapping to the FPGA includes the size of the area to be mapped and communication issues related to their communication. Area size selection is compared to the page size selection in Operating System Design. Communication issues between modules are compared to the software engineering paradigms dealing with module coupling, fan-in, fan-out and cohesiveness. Finally, the overhead associated with the downloading of the reconfiguration files is discussed.